2004
DOI: 10.1074/jbc.m407259200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Swi6/HP1-dependent Heterochromatin Assembly by Cooperation of Components of the Mitogen-activated Protein Kinase Pathway and a Histone Deacetylase Clr6

Abstract: A study of gene silencing within the mating-type region of fission yeast defines two distinct pathways responsible for the establishment of heterochromatin assembly. One is RNA interference-dependent and acts on centromere-homologous repeats (cenH). The other is a stochastic Swi6 (the fission yeast HP1 homolog)-dependent mechanism that is not fully understood. Here we find that activating transcription factor (Atf1) and Pcr1, the fission yeast bZIP transcription factors homologous to human ATF-2, are crucial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 45 publications
2
127
0
Order By: Relevance
“…Subsequently, multimerization of Swi6 together with an interaction with the histone methyltransferase Clr4 helps in spreading the heterochromatin. (Alternative pathways exist where Atf1-mediated recruitment of Clr4 occurs independently of RNAi (29,40).) Swi6, in turn, recruits the Cohesin complex, which is important for sister chromatid cohesion and for imparting greater chromatin integrity to the mating type region.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, multimerization of Swi6 together with an interaction with the histone methyltransferase Clr4 helps in spreading the heterochromatin. (Alternative pathways exist where Atf1-mediated recruitment of Clr4 occurs independently of RNAi (29,40).) Swi6, in turn, recruits the Cohesin complex, which is important for sister chromatid cohesion and for imparting greater chromatin integrity to the mating type region.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the levels of both Atf1 and Pcr1 proteins are expected to be elevated in stress conditions. Atf1/Pcr1 factors have been shown to target Swi6 and Clr4 to the silent domain through their physical interaction with these proteins (Jia et al, 2004;Kim et al, 2004). These factors are critical for deacetylation of H3 and H4 histones and the dosage-critical role of Swi6 in silencing is dependent upon the presence of Atf1 (Kim et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that two independent pathways operate to nucleate heterochromatin assembly at the mat2,3 region (Grewal and Jia, 2007). One of these pathways is through stress-activated ATF/CREB family proteins, Atf1 and Pcr1 (Jia et al, 2004;Kim et al, 2004); the other involves the RNAi machinery (Hall et al, 2002).…”
Section: G Singh and A J S Klarmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ATF/CREB family proteins Atf1 and Pcr1 cooperate with RNAi to establish heterochromatin at the silent mating type region (Jia et al 2004;Kim et al 2004). Similarly, telomere shelterin component Taz1 and the telomere-associated sequence (TAS) function together with RNAi to establish heterochromatin at telomeres (Kanoh et al 2005).…”
mentioning
confidence: 99%